Solvent-free, Environmentally Benign Syntheses of Some Imines and Antioxidant Activity - Zangade, Sainath B.; Shinde, Avinash; Chavan, Shivaji; Vibhute, Yeshwant (Orbital: The Electronic Journal of Chemistry, 2015)
Environmentally benign, economically feasible, and solvent-free syntheses of series of imines by the condensation of a substituted hydroxynaphthyl ketone with several substituted iodoanilines under grinding approach are described. Imines were further tested for antioxidant activity; most of them show moderate activity.DOI: http://dx.doi.org/10.17807/orbital.v7i3.608